Evidences for a Nutritional Role of Iodine in Plants - Kiferle, Claudia; Martinelli, Marco; Salzano, Anna Maria; Gonzali, Silvia; Beltrami, Sara; Salvadori, Piero Antonio; Hora, Katja; Holwerda, Harmen Tjalling; Scaloni, Andrea; Perata, Pierdomenico (Frontiers in Plant Science, 2021)
Little is known about the role of iodine in plant physiology. We evaluated the impact of low concentrations of iodine on the phenotype, transcriptome and proteome of Arabidopsis thaliana. Our experiments showed that removal of iodine from the nutrition solution compromises plant growth, and restoring it in micromolar concentrations is beneficial for biomass accumulation and leads to early flowering. In addition, iodine treatments specifically regulate the expression of several genes, mostly involved in the plant defence response, suggesting that iodine may protect against both biotic and abiotic stress. Finally, we demonstrated iodine organification in proteins. Our bioinformatic analysis of proteomic data revealed that iodinated proteins identified in the shoots are mainly associated with the chloroplast and are functionally involved in photosynthetic processes, whereas those in the roots mostly belong and/or are related to the action of various peroxidases. These results suggest the functional involvement of iodine in plant nutrition.